Atomic resolution description of the interaction between the nucleoprotein and phosphoprotein of Hendra virus. - Guillaume Communie (Public Library of Science (PLoS), 2013)
Hendra virus (HeV) is a recently emerged severe human pathogen that belongs to the Henipavirus genus within the Paramyxoviridae family. The HeV genome is encapsidated by the nucleoprotein (N) within a helical nucleocapsid. Recruitment of the viral polymerase onto the nucleocapsid template relies on the interaction between the C-terminal domain, N(TAIL), of N and the C-terminal X domain, XD, of the polymerase co-factor phosphoprotein (P). Here, we provide an atomic resolution description of the intrinsically disordered N(TAIL) domain in its isolated state and in intact nucleocapsids using nuclear magnetic resonance (NMR) spectroscopy. Using electron microscopy, we show that HeV nucleocapsids form herringbone-like structures typical of paramyxoviruses. We also report the crystal structure of XD of P that consists of a three-helix bundle. We study the interaction between N(TAIL) and XD using NMR titration experiments and provide a detailed mapping of the reciprocal binding sites. We show that the interaction is accompanied by α-helical folding of the molecular recognition element of N(TAIL) upon binding to a hydrophobic patch on the surface of XD. Finally, using solution NMR, we investigate the interaction between intact nucleocapsids and XD. Our results indicate that monomeric XD binds to N(TAIL) without triggering an additional unwinding of the nucleocapsid template. The present results provide a structural description at the atomic level of the protein-protein interactions required for transcription and replication of HeV, and the first direct observation of the interaction between the X domain of P and intact nucleocapsids in Paramyxoviridae.